Municipal Geothermal Systems: Evaluation of Three Hungarian Cases - Szolga, Krisztián; Árpád, István W.; Kocsis, Dénes (International Journal of Engineering and Management Sciences, 2024)
Geothermal energy holds great potential for a sustainable future, as it is a clean and weather-independent form of energy. In addition to energy production, it can also serve the population of a region through direct use. In this paper, three municipal geothermal systems (Szarvas, Nagyszénás, Békéscsaba) in the same Hungarian region which have been recently installed or expanded are presented and analysed. Here, the direct usage of geothermal energy for heating purposes is a very important issue. The three systems show several differences and to some extent face different challenges in the various phases of the projects. Particular attention has been paid to engineering solutions to the problems that arise. The challenges, such as technical difficulties during installation, maintenance difficulties, or problems arising during operation are introduced. The strengths, weaknesses, opportunities, and threats of similar geothermal systems were summarized, based on the relevant literature. These points were evaluated by their appearance and characteristics in the examined systems. This study aims to provide insights, based on recently gained experiences, into geothermal projects, thus providing feedback and practical information for researchers and practitioners.